An Integrated Model for Predicting Engine Friction Losses in Internal Combustion Engines - Kamil, Mohammed; M. M., Rahman; R. A., Bakar (Universiti Malaysia Pahang, 2014)
A comprehensive computer model (EFLP) has been developed for carrying out friction estimation and analysis of sparks ignited in reciprocating engines. EFLP considers five major loss components in an automotive engine: the crankshaft, piston, valvetrain, auxiliary components and pumping losses. Hydrodynamic, mixed, and boundary layer regimes are used to model the friction phenomena. The main building blocks of EFLP are empirical engine friction models based on experimental data. EFLP is constructed using MATAB-based engine code for estimating engine performance. The friction in a 4-cylinder 4-stroke engine is inspected. The results predicted by EFLP were validated according to a case study available in the literature. The validation showed that EFLP predictions are realistic and accurate.